A model of care for healthy menopause and ageing: EMAS position statement. (October 2016) - Stute, Petra; Ceausu, Iuliana; Depypere, Herman; Lambrinoudaki, Irene; Mueck, Alfred; Pérez-López, Faustino R.; van der Schouw, Yvonne T.; Senturk, Levent M.; Simoncini, Tommaso; Stevenson, John C.; Rees, Margaret
Highlights: The conceptual framework of the Healthy Menopause and Ageing is a holistic model of care incorporating disease and disability. Healthcare model's core: lead clinician, specialist nurse, patient, interdisciplinary network of health and allied health professionals. Provision of specialist teams in Europe needs to be expanded, as the number of women ("baby-boomers") currently reaching menopause is increasing. Accreditation of the subspecialty Women's Health should be actively promoted. Abstract: Worldwide, the number of menopausal women is increasing. They present with complex medical issues that lie beyond the traditional scope of gynaecologists and general practitioners (GPs). The European Menopause and Andropause Society (EMAS) therefore provides a holistic model of care for healthy menopause (HM). The HM healthcare model's core consists of a lead clinician, specialist nurse(s) and the woman herself, supported by an interdisciplinary network of medical experts and providers of alternative/complementary medicine. As HM specialist teams are scarce in Europe, they are also responsible for structuring and optimizing processes in primary care (general gynaecologists and GPs) and secondary care (HM specialists). Activities for accreditation of the subspecialty Women's Health are encouraged.